Reliability of WHOQOL-BREF in studies conducted in women with breast cancer: integrative review - Martín del campo- Navarro, Valeria (Universidad de Sonora, 2022)
Introduction: The quality of life in women with breast cancer due to its complex multidimensionality has been measured with both specific and generic questionnaires. Objective: Determine the reliability of the World Health Organization's Quality of Life Questionnaire in studies conducted in women with breast cancer. Methodology: Integrative review of original articles, in databases such as PubMed, SciELO, Virtual Health Library, Web of Science, with the descriptors Breast neoplasms, WHO’s Quality of Life, along with the boolean AND. Articles that showed reliability of the World Health Organization’s Quality of Life questionnaire were included; they were applied to women with breast cancer, free on the web, full text, in English, Portuguese, or Spanish, published between 2009 and 2019. Studies in women with breast cancer with added pathology were excluded. A sample of 8 articles was obtained. Results: 37.5% of the studies assessed gave an overall Cronbach's alpha ranging between 0.72 and 0.84 with mean α=0.79. The articles that performed the domains reported 0.77 as mean reliability in physical health, 0.77 in psychological health, 0.76  in social relationships, and 0.72 in environment, thus, demonstrating an appropriate reliability. Conclusion: The reliability through Cronbach's alpha for the domains of the Quality of Life Questionnaire does not varies depending on the stage of the disease process, indicating the relevance of using the questionnaire in women with breast cancer.